Upaya Meningkatkan Hasil Belajar Materi Bangun Ruang Sisi Lengkung Melalui Metode Discovery Learning Pada Siswa Kelas IX SMP Negeri 1 Dukun Tahun Pelajaran 2018/2019 - Grace Kumowal, Jeanette (Science and Education Journal (SICEDU), 2022)
One of the problems in learning mathematics is the weak ability of students to apply knowledge to solve problems in real life, especially in solving problems in Geometry. In an effort to solve this problem, Classroom Action research was carried out, using the Discovery learning Model. This study aimed to improve the learning achievement of class IX D SMP N Dukun in 2018-2019 using the Discovery learning model. The research subjects were 30 students, the source of research data was obtained from qualitative data in the form of data from observations of teacher and student activities and quantitative data in the form of test data on student learning outcomes. The results of the first cycle research were obtained by students who completed individually as many as 24 students with classical completeness of as much as 80%. While the second cycle of research increased with the number of students who completed individually as many as 30 students with a 100% completeness percentage. With the results of this study, learning using the Discovery learning model can improve the learning outcomes of class IX D students at SMPN Dukun for the 2018-2019 school year.